Combined Nasal, Oropharyngeal Povidone Iodine Plus Glycyrrhizic Acid Sprays, Accelerate Clinical and Laboratory Recovery and Reduces Household Transmission of SARS-CoV-2: A Randomized Placebo-Controlled Clinical Trial - Elsersy, Hazem E.; Zahran, Magdy A. H.; Elbakry, Abd-Elazeem; Abd-Elwahab, Mohamed; Ahmed, Mohamed Milegy; Elgandy, Mohamed Salah; Mohammed, Eman H. M.; Elewa, Nourhan M. (Frontiers in Medicine, 2022)
The COVID-19 pandemic is still posing challenging health and economic problems. Effective broad-spectrum antiviral therapy is urgently needed for the control of early SARS-COV2 infection to limit its spread and mutations. In this randomized placebo-controlled clinical study, we tested the effects of intranasal and oropharyngeal delivery of a compound of povidone iodine 0.5% and glycyrrhizic acid 2.5 mg/ml on the laboratory (PCR) and clinical recovery from SARS-COV2 patients and their household contacts. Three hundred fifty-three patients suspected of having COVID infection were screened by chest CT and nasopharyngeal swab tests (PCR). Two hundred patients were randomly allocated to two equal groups: treatment and placebo groups. Treatment accelerated the recovery of PCR on days 4, 7 and 10, as evidenced by PCR-positive patients (70%, versus 99%, 20% versus 65%, 1% versus 10%) in both the treated and placebo groups, respectively. Treatment enhanced the early recovery of symptoms (day 7.6±2 [CI 7:8.3] versus 8.9±2 [CI 8.3:9.6]). Treatment promoted early recovery of anosmia and ageusia (5.6±1 [CI, 4.8:6.4] versus 11±3 days, [CI, 10.8:12]) in both the treated and control groups (P<0.0001). There was a notable reduction in transmission of the virus among the household close contacts in the treatment group (4%) versus 76% in the placebo group. Combined PVI-GA nasal and oropharyngeal spray accelerates both laboratory and clinical recovery of SARS-COV2-infected patients in the early phases of the disease and reduces household spread of the virus; thus, it may play an important role in controlling coronavirus outbreaks. Keywords. Acid Glycyrrhizic, Iodine povidone, Antiviral SARS-COV2, Nasal spray, Oropharyngeal spray.